How Many Regional Medical Centers Can Maine Sustain? How Patient Hospital Utilization Can Help Define Structure - Rydell, Lars (Maine Policy Review, 2004)
Making thoughtful decisions about where various levels of hospital care are to be provided is an important part of controlling overall healthcare costs. Efficient utilization of healthcare resources requires that high-cost and less frequently used high-tech equipment and specialized personnel should be limited to a few tertiary regional medical centers. Lars Rydell uses patient discharge data from the Maine Health Data Organization to suggest that Maine currently has only two hospitals that function as tertiary regional medical centers—Maine Medical Center in Portland and Eastern Maine Medical Center in Bangor. Policymakers need to think about whether Maine’s population base warrants more than two such centers.